Fıkıh usulünde haram kavramı - Uğur, Seyit Mehmet (My University, 2009)
Tez adı: Fıkıh Usulünde Haram Kavramı Hazırlayan: Seyit Mehmet Uğur Bir hadiste “Allah’ın korusu” olarak nitelenen haramlar, mükelleflerin kesinlikle uzak durmaları ve asla içine düşmemeleri gereken alana işaret eder. Haramlardan sakınmak, fert ve toplumun, dünyevî ve uhrevî selâmeti açısından hayati öneme sahiptir. Bu açıdan, bir hüküm mertebesi olarak haramın mâhiyetinin bilinmesinin ehemmiyeti açıktır. Teklîfî bir hüküm olarak haramın ne olduğunu ve haram hükmüne nasıl ulaşılacağına ilişkin kuralları esas itibariyle fıkıh usulü ortaya koyar. Fıkıh usulü eserlerinde haram kavramının nasıl incelendiğini ve haramla ilgili hangi mesele ve tartışmalara yer verildiğini araştırdığımız bu çalışmamızın giriş bölümünde kısaca yasak olgusundan bahsettik. Birinci bölümde ise esas itibariyle haramın ne olduğunu ortaya koymaya çalıştık. Bunu yaparken önce haramla eş ya da yakın anlamda kullanılan kavramları inceledik. Daha sonra haram tarif ve taksimlerini incelemek suretiyle haramın mâhiyetini tespite çalıştık. Yine bu amaçla haramı diğer teklîfî hükümlerle mukâyese ettik. Çalışmamızın ikinci bölümünde ise temel olarak haramın menşeîni ve müctehidin haram hükmünü nasıl elde ettiğini araştırdık. Bunun için, haram kılmaya yetkili mercî meselesine ve bu konu etrafındaki bazı tartışmalara yer verdik. Daha sonra haram hükmünün naslarda beyan ediliş üsluplarını ve haramın hangi şerî delillerle sabit olabileceğini inceledik. Son olarak haram kılmanın hedef ve gerekçelerini ve haramla ilgili birtakım ilkeleri ele aldık.

THE NAME OF THE THESIS: The Concept of Haram in Islamic Jurisprudence THE WRITER: Seyit Mehmet Ugur. Haram that is described as God’s grove by a hadith means that responsible people have to avoid them. It is crucial for an individual and society to avoid them in order to obtain happiness in the world and another world. For that reason, the importance of knowing the content of haram as a grade of Islamic legal provision is apparent. In essence Usul al Fiqh (the methodology of Islamic law) deals with the rules pertaining to what haram is as a taqlifi provision and how haram provision can be received. I have mentioned briefly the phenomenon of haram in the introduction of our thesis, in which I have studied how the concept of haram is examined in the literature of Usul al fıqh and what matters related to haram there are and discussions concerning haram have taken place. In fact, I have tried to explain what haram is in the first chapter. While doing that, at first, I have examined the synonymies of haram and the concepts that are used with the similar meaning to haram. Then, by studying the definitions and categories of haram we have tried to explain what haram is. Furthermore, for the same goal, we have compared and contrasted haram with the others of the taqlifi provisions. We have examined the origin of haram and how Islamic scholars have received haram provision in the second chapter. For that, we have mentioned the issue of who has the authority to make something haram and some debates related to this subject. Moreover, we have examined how haram provision is explained in Islamic texts (nass) and by what Islamic proofs we can say that this is haram. In consequence, we have tackled what the aim of making something haram is, what the reasons for it are and the principles as regards haram.
Keywords: Fıkıh; İslam Dini; İslam Hukuku